An evaluation of large diameter through-thickness metallic pins in composites - Neale, Geoffrey; Saaran, Vinodhen; Dahale, Monali; Skordos, Alexandros A. (Elsevier, 2024)
There is increasing demand for functional through-thickness reinforcement (TTR) in composites using elements whose geometry exceeds limitations of existing TTR methods like tufting, stitching, and z-pinning. Recently, static insertion of large diameter TTR pins into heated prepreg stacks has proven a feasible and robust reinforcement process capable of providing accurate TTR element placement with low insertion forces and lower tow damage compared with existing methods for similar element sizes (>1mm diameter) like post-cure drilling. Local mechanical performance and failure mechanics of these pinned laminates are reported here. Laminates with a single statically inserted pins (1.2, 1.5, and 2.0 mm) can mostly retain their in-plane integrity alongside a local improvement in mode I delamination toughness in carbon fibre-benzoxazine laminates. Tensile strength is mostly unaffected by the pins resulting from delamination suppression, whereas there is up to a doubling of Young’s modulus. Compressive strength is significantly diminished (up to 42 %) in pinned laminates. Interlaminar toughness is improved, and peak toughness is pushed ahead of the crack as pin diameter increases. The lack of significant deterioration in in-plane tensile properties in pinned laminates produced using static insertion can expand the range and forms of materials that can be inserted compared to existing TTR.
Keywords: Through-thickness reinforcement; Carbon fibre; Benzoxazine; Damage mechanics; Finite element analysis (FEA)